2020
DOI: 10.1158/1078-0432.ccr-19-4055
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Acetyl-CoA Carboxylase Is Associated with Clinical Benefit with Regorafenib in Relapsed Glioblastoma: REGOMA Trial Biomarker Analysis

Abstract: Purpose: Preclinical studies show that antiangiogenic therapy exacerbates tumor glycolysis and activates liver kinase B1/AMP kinase (AMPK), a pathway involved in the regulation of tumor metabolism. We investigated whether certain metabolism-related in situ biomarkers could predict benefit to regorafenib in the phase II randomized REGOMA trial.Patients and Methods: IHC and digital pathology analysis were used to investigate the expression in glioblastoma (GBM) sections of monocarboxylate transporter 1 and 4 (MC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…However, before using gene amplification results for clinical decision-making, it is best to use other molecular analyses for proper clinical validation to guide targeted therapy in glioblastoma. 52,53 Herein, we found that the frequency of CNV events in high-grade gliomas was significantly higher than in low-grade tumors, and the recurrence group had significantly more CNV events than the initial treatment group. Previous studies have found that the existence of EGFR amplification in CNV analysis was significantly associated with both worse disease-free survival (DFS) and overall survival (OS) in gliomas.…”
Section: Discussionmentioning
confidence: 78%
“…However, before using gene amplification results for clinical decision-making, it is best to use other molecular analyses for proper clinical validation to guide targeted therapy in glioblastoma. 52,53 Herein, we found that the frequency of CNV events in high-grade gliomas was significantly higher than in low-grade tumors, and the recurrence group had significantly more CNV events than the initial treatment group. Previous studies have found that the existence of EGFR amplification in CNV analysis was significantly associated with both worse disease-free survival (DFS) and overall survival (OS) in gliomas.…”
Section: Discussionmentioning
confidence: 78%
“…Unfortunately, we did not perform an exploratory analysis to study some predictors of efficacy; indeed, two prior studies have investigated the role of molecular predictors of regorafenib efficacy in the REGOMA trial: a mini-signature of 2 gene transcripts (HIF1A, CDKN1A), 3 miRNAs (miR-3607-3p, miR-301a-3p, miR-93-5p) [ 26 ] and phosphorylated acetyl-CoA carboxylase [ 27 ] were associated with prolonged survival in recurrent glioblastoma patients treated with regorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, NCCN 2020 guidelines included regorafenib as a preferred regimen in rGBM patients and the Italian Agency of Medicine (AIFA) approved the use of this treatment for Italian patients. Two subsequent studies demonstrated a higher efficacy of regorafenib in selected patients with specific molecular alterations such as phosphorylated acetyl-CoA carboxylase [129,130]. Dovitinib, an oral FGFR, VEGFR and PDGFRβ inhibitor, was analyzed in another phase II study [87] where dovitinib was tested in two different populations of rGBM patients: anti-angiogenetic naive patients and anti-angiogenetic drug pretreated patients; however, results showed poor efficacy in terms of prolonging PFS (primary endpoint): mPFS was 2.0m (95% CI, 1.3-3.7) for anti-angiogenic naïve patients versus 1.8m (95% CI, 0.9-1.8) for anti-angiogenic pretreated patients (p = 0.03).…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%